Hindbrain REV-ERB nuclear receptors regulate sensitivity to diet-induced obesity and brown adipose tissue pathophysiology - Lauren N. Woodie; Lily C. Melink; Ahren J. Alberto; Michelle Burrows; Samantha M. Fortin; Calvin C. Chan; Matthew R. Hayes; Mitchell A. Lazar (Elsevier, 2024)
Objective: The dorsal vagal complex (DVC) of the hindbrain is a major point of integration for central and peripheral signals that regulate a wide variety of metabolic functions to maintain energy balance. The REV-ERB nuclear receptors are important modulators of molecular metabolism, but their role in the DVC has yet to be established. Methods: Male REV-ERBα/β floxed mice received stereotaxic injections of a Cre expressing virus to the DVC to create the DVC REV-ERBα/β double knockout (DVC RDKO). Control littermates received stereotaxic injections to the DVC of a green fluorescent protein expressing virus. Animals were maintained on a normal chow diet or a 60% high-fat diet to observe the metabolic phenotype arising from DVC RDKO under healthy and metabolically stressed conditions. Results: DVC RDKO animals on high-fat diet exhibited increased weight gain compared to control animals maintained on the same diet. Increased weight gain in DVC RDKO animals was associated with decreased basal metabolic rate and dampened signature of brown adipose tissue activity. RDKO decreased gene expression of calcitonin receptor in the DVC and tyrosine hydroxylase in the brown adipose tissue. Conclusions: These results suggest a previously unappreciated role of REV-ERB nuclear receptors in the DVC for maintaining energy balance and metabolic rate potentially through indirect sympathetic outflow to the brown adipose tissue.